Associated Clustering Strategy for Wireless Sensor Network - Yajuan Sun; Huanzhao Wang; Kewang Zhang; Xudong Yang (International Journal of Distributed Sensor Networks)
We consider the soil moisture monitoring problem and propose a WSN associated clustering strategy based on spatiotemporal data correlation, which ensures that the nodes within each cluster can share a good data correlation and consequently makes the cluster head do the data fusion more efficiently. As a result, the energy of each node will be saved and the lifetime of the whole sensor network will be extended. In the associated clustering strategy, the different clusters can be divided by the correlation characteristics of nodes data, which is based on a dynamic model and a correlation characteristics model after the correlation coefficient analysis. Simulation results show that our proposed associated clustering strategy works very well in soil moisture measurement. Moreover, as compared with the traditional random clustering, the associated clustering strategy based on data correlation achieves better performance for each cluster, and will be more efficient in data fusion at the cluster heads.